2021
DOI: 10.1038/s41524-021-00536-2
|View full text |Cite
|
Sign up to set email alerts
|

Analogical discovery of disordered perovskite oxides by crystal structure information hidden in unsupervised material fingerprints

Abstract: Compositional disorder induces myriad captivating phenomena in perovskites. Target-driven discovery of perovskite solid solutions has been a great challenge due to the analytical complexity introduced by disorder. Here, we demonstrate that an unsupervised deep learning strategy can find fingerprints of disordered materials that embed perovskite formability and underlying crystal structure information by learning only from the chemical composition, manifested in $$({{\rm{A}}}_{1-{\rm{x}}}{{\rm{A}}^{\prime} }_{{… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Recently, we have shown that quantifying materials analogies can accelerate target driven discovery of materials. [ 14 ] Such analogies rely on stoichiometry‐derived global material embeddings. Incorporating EAMs that reflect interactions between atoms adds another dimension for materials similarity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that quantifying materials analogies can accelerate target driven discovery of materials. [ 14 ] Such analogies rely on stoichiometry‐derived global material embeddings. Incorporating EAMs that reflect interactions between atoms adds another dimension for materials similarity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The dominance of ML in materials informatics propelled by curated databases is evident not only because of successful instances in new materials discovery, but also due to its significant impact on every step of material design hierarchy. [ 4 , 5 , 6 , 7 ] This includes replacing first‐principles calculations, [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] optimal design of experiments, [ 15 , 16 , 17 ] material characterization, [ 18 , 19 , 20 ] and improved understanding of material phenomena. [ 21 , 22 , 23 ] While hand‐crafted material descriptors may warrant uniqueness and invariance to translations, rotations, and permutations of constituents, the performance of ML models is heavily reliant on how fine the descriptor is and the level of chemical and structural information captured.…”
Section: Introductionmentioning
confidence: 99%
“…Discoveries of novel tunable and phase changing materials are urgently needed and accelerated by ML and artificial intelligence. [ 51 ] Hologram metasurfaces seem to be common for all spectra for applications including camouflage, even for acoustic waves. Finally, “additive manufacturing” ranging from 3D/4D printing to roll‐to‐roll (R2R) processing has become a key technological enabler, which sustains the growing trend of metamaterial research.…”
Section: Clustering Abstractmentioning
confidence: 99%
“…Moreover, we note that are not alone in the literature when it comes to leveraging SISSO to generate models of perovskite properties -the last several years have seen success in the creation of models of perovskite properties with this tool. The work of Xie et al [60] achieved good success in predicting the octahedral tilt in ABO 3 perovskites, the work of Bartel et al [59] resulted in the creation of a new tolerance factor for ABX 3 perovskite formation, and Ihalage and Hao [58] leveraged descriptors generated by SISSO to predict the formation of quaternary perovskites with formula (A 1−x A x )BO 3 and A(B 1−x B x )O 3 .…”
Section: Perovskite Volume Per Formula Unitmentioning
confidence: 99%
“…SISSO also generates equations mapping descriptors to a target property, proceeding by combining descriptors using various building blocks, including trigonometric functions, logarithms, addition, multiplication, exponentiation, and many others. This methodology has been highly successful in a variety of areas including crystal structure classification [57] , as well as the prediction of perovskite properties [58][59][60] and 2D topological insulators [61] .…”
Section: Introductionmentioning
confidence: 99%